Clinical Effect of Open Reduction and Internal Fixation for Femoral Neck Fracture in Young Adults and Related Factors of Femoral Head Necrosis. (4th October 2022) - Lin, Guanghui; Yang, Dongliang; Sui, Wei
Abstract : Objective . The purpose of this article is to analyze the clinical effect of open reduction and internal fixation on femoral neck fracture in young adults and to explore the related factors of femoral head necrosis. Methods . The subjects were young and middle-aged femoral neck fracture patients admitted to our hospital from July 2019 to July 2021. 90 patients were randomly divided into two groups according to different treatment methods. The control group (n = 45 ) was treated with open reduction and internal fixation with hollow nails, while the observation group (n = 45 ) was treated with closed reduction and internal fixation with hollow nails. The clinical effects and adverse reactions of the two groups and the risk factors of avascular necrosis of femoral head were analyzed. Results . Compared with the control group, the operation time of the observation group was significantly shortened (P < 0.05 ), the amount of bleeding during the operation was significantly reduced (P < 0.05 ), and the incidence of total adverse reactions was significantly reduced (P < 0.05 ). The HSS score and Harris score of the two groups were significantly decreased after treatment (P < 0.05 ), but there was no significant difference in the above scores between the two groups before and after treatment (P > 0.05 ). The related risk factors of necrosis included gender, Garden classification, time from injury to operation, and time of weight bearing after operation (P < 0.05 ) but not related to age and cause of injury (P > 0.05 ). Conclusion. Open and closed reduction and internal fixation can effectively treat femoral neck fracture in young adults. The risk factors of adverse reactions of osteonecrosis include gender, Garden classification, time from injury to operation, and weight-bearing time after operation.